Hybrid intelligent control strategy. Supervising a DCS-controlled batch process. - Han-Xiong Li
In industrial control, it frequently happens that, while the low-level controller performs very well, high-level supervision is required to maintain good overall performance that is usually beyond the capability of direct machine control. A hybrid control methodology combining conventional and intelligent techniques has been introduced to replace human supervision for a DCS-controlled laminar cooling process. The industrial experiments show the improved performance of the proposed hybrid control model and confirm its validity in a real manufacturing environment. The results can be extended to a wide range of processes with similar features. The methodology is superior in terms of high performance, reliability, simplicity and ease of construction
Keywords: DCS; Batch process; Direct machine control; Distributed control; High-level supervision; Hybrid intelligent control strategy; Industrial control; Laminar cooling process; Manufacturing environment; Reliability; Supervisory control